PEMANFAATAN TEKNOLOGI AUGMENTED REALITY DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR (UTILIZATION OF AUGMENTED REALITY TECHNOLOGY IN SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOL) - Rahman, Septia; Chairunisa, Amelia Tatum; Dianti, Putri; Marini, Arita; Yunus, Mahmud (Cahaya Ilmu Bangsa Institute, 2024)
The development of technology that continues to grow continues to affect every area of our lives. Currently, the field of education is also not immune from the influence of technology in its innovation to continue to provide innovative and fun learning for students, such as the use of Augmented Reality technology in social studies learning in elementary schools. The purpose of this research is to find out how the utilization of AR technology is applied in learning in elementary schools, especially in social studies subjects. The research method used is a literature study conducted to collect library data, read and record important information found and manage it systematically and analytically regarding the Utilization of Augmented Reality Technology in Social Studies Learning in Elementary Schools. From the discussion, the results show that learning social studies in elementary schools using Augmented Reality (AR) technology can increase student involvement in learning because students can interact with images, simulations, and interesting 3D objects, providing a more real and contextual experience of the learning material presented. However, despite the positive benefits, AR still has limitations in terms of implementation costs, infrastructure availability, and teacher readiness and technical ability in integrating AR into learning. Perkembangan teknologi yang terus berkembang terus mempengaruhi tiap bidang kehidupan kita. Saat ini, bidang Pendidikan juga tidak luput dari pengaruh teknologi dalam inovasinya untuk terus memberikan pembelajaran yang inovatif dan menyenangkan bagi para siswa, seperti contohnya penggunaan teknologi Augmented Reality dalam pembelajaran IPS di SD. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pemanfaatan teknologi AR diterapkan dalam pembelajaran di sekolah dasar, khususnya pada mata Pelajaran IPS. Metode penelitian yang digunakan adalah studi literatur yang dilakukan untuk mengumpulkan data pustaka, membaca serta mencatat informasi penting yang ditemukan serta mengelolanya secara sistematis dan analitis tentang mendapatkan manfaat dari teknologi berbasis Augmented Reality dalam proses belajar mengajar IPS di tingkat Sekolah Dasar. Dari pembahasan, diperoleh manfaat bahwa proses belajar mengajar IPS di SD dibantu pemanfaatan teknologi Augmented Reality (AR) dapat memperkuat partisipasi siswa dalam proses belajar-mengajar karena mereka memiliki kesempatan untuk berinteraksi dengan visual, simulasi, serta objek 3D yang menarik, memberikan pengalaman yang lebih nyata dan kontekstual terhadap materi pembelajaran yang disampaikan. Namun, di samping manfaat positifnya tersebut, AR masih memiliki keterbatasan dalam aspek biaya implementasi, ketersediaan infrastruktur, serta kesiapan dan kemampuan teknis guru dalam mengintegrasikan AR di dalam proses kegiatan belajar mengajar.